The timing of breeding and independence for snow leopard females and their cubs - Örjan Johansson; Giorgia Ausilio; Matthew Low; Purevjav Lkhagvajav; Byron Weckworth; Koustubh Sharma (Mammalian Biology, 2021)
Significant knowledge gaps persist on snow leopard demography and reproductive behavior. From a GPS-collared population in Mongolia, we estimated the timing of mating, parturition and independence. Based on three mother–cub pairs, we describe the separation phase of the cub from its mother as it gains independence. Snow leopards mated from January–March and gave birth from April–June. Cubs remained with their mother until their second winter (20–22 months of age) when cubs started showing movements away from their mother for days at a time. This initiation of independence appeared to coincide with their mother mating with the territorial male. Two female cubs remained in their mothers’ territory for several months after initial separation, whereas the male cub quickly dispersed. By comparing the relationship between body size and age of independence across 11 solitary, medium-to-large felid species, it was clear that snow leopards have a delayed timing of separation compared to other species. We suggest this may be related to their mating behavior and the difficulty of the habitat and prey capture for juvenile snow leopards. Our results, while limited, provide empirical estimates for understanding snow leopard ecology and for parameterizing population models.